Instability of a swirling bubble ring - Xu, Yonghui; Delbende, Ivan; Fuster, Daniel; Rossi, Maurice (Comptes Rendus. Mécanique, 2020)
A toroidal bubble or a cylindrical gas jet are known to be subjected to the Rayleigh–Plateau instability. Air bubble rings produced by beluga whales and dolphins however are observed that remain stable for long times. In the present work, we analyse the generation of such toroidal bubbles via numerical simulations, in particular how the process depends on surface tension. Their stability properties are then briefly analysed. For the estimated Reynolds and Weber numbers relative to the bubbles produced by these animals, the presence of a vortex inside and around the bubble is found to strongly stabilize the Rayleigh–Plateau instability.